2023
DOI: 10.1371/journal.pone.0282158
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the intelligent-auxiliary design of architectural space using artificial intelligence model

Abstract: In order to carry out a comprehensive design description of the specific architectural model of AI, the auxiliary model of AI and architectural spatial intelligence is deeply integrated, and flexible design is carried out according to the actual situation. AI assists in the generation of architectural intention and architectural form, mainly supporting academic and working theoretical models, promoting technological innovation, and thus improving the design efficiency of the architectural design industry. AI-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In addition, with the help of AI technology, through the adjustment and optimization of keywords, AI automatically generates a number of architectural space design schemes. The auxiliary model of architectural space design is established, and the literature research is carried out through the analysis of AI model, intelligent auxiliary model of architectural space, semantic network and internal structure of architectural space [ 33 ]. This echoes the research of Li et al (2023), who emphasized that AI can automatically generate a number of architectural space design schemes by adjusting and optimizing keywords.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, with the help of AI technology, through the adjustment and optimization of keywords, AI automatically generates a number of architectural space design schemes. The auxiliary model of architectural space design is established, and the literature research is carried out through the analysis of AI model, intelligent auxiliary model of architectural space, semantic network and internal structure of architectural space [ 33 ]. This echoes the research of Li et al (2023), who emphasized that AI can automatically generate a number of architectural space design schemes by adjusting and optimizing keywords.…”
Section: Discussionmentioning
confidence: 99%
“…With the introduction of AI technology products in the market and the increasing popularity of AI-powered conversational models like ChatGPT, more and more people are paying attention to the impact of AI on the architecture design industry. Hongyu Li et al [28] analyzed the data transmission process of architectural space models based on semantic networks and architectural spatial structure analysis. The fitting curves of the comprehensive model demonstrated that AI-based intelligent architectural spatial design solutions outperformed traditional architectural design solutions.…”
Section: Integration Of Ai In Architectural Visualization Designmentioning
confidence: 99%
“…The convergence of Artificial Intelligence (AI) and architecture is a revolutionary era in how we conceptualize, design, and construct our physical surroundings (As et al, 2018;Li et al, 2023;Wang and Chen, 2022;Castro Pena et al, 2021;Ji, 2022). Key players in this transformation include generative models like ChatGPT and Bard, which have become influential in reshaping the architectural landscape (Raza et al, 2023;Çaliskan, 2023;Abrusci et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The infusion of generative AI into architectural theory marks a paradigm shift, redefining the essence of creativity in architectural design (Li et al, 2023;Castro et al, 2021). Traditional theories centered on human intuition and experience, but the integration of AI introduces a compelling blend of machine intelligence and human ingenuity (Zhang, 2022;Cudzik and Radziszewski, 2018;Chen et al, 2023;Sönmez, 2018;Winiarti et al, 2022).…”
Section: Introductionmentioning
confidence: 99%